2015
DOI: 10.1016/j.bjp.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Stevia rebaudiana loaded titanium oxide nanomaterials as an antidiabetic agent in rats

Abstract: Revista Brasileira de Farmacognosia 25 (2015) [145][146][147][148][149][150][151] w w w . s b f g n o s i a . o r g . b r / r e v i s t a a b s t r a c t Stevia rebaudiana (Bertoni) Bertoni, Asteraceae, is a plant with hypoglycemic and antihyperlipidemic properties. S. rebaudiana (SrB) has become a lead candidate for the treatment of the diabetes mellitus. However, chronic administrations of S. rebaudiana are required to cause the normoglycemic effect. Importantly, nanomaterials in general and titanium dioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The results of α-amylase inhibition as shown in Figure 11 demonstrate undoped TiO 2 nanoparticles and N-doped TiO 2 nanoparticles to be the potent candidates against diabetes mellitus. Previously, Stevia rebaudiana loaded TiO 2 nanoparticles have been proved potential antidiabetic agents via in vivo studies performed in rats [40]. N-doped TiO 2 nanoparticles possess more significant α-amylase inhibition (38.2%) as compared to bare TiO 2 nanoparticles (24.8%).…”
Section: Resultsmentioning
confidence: 99%
“…The results of α-amylase inhibition as shown in Figure 11 demonstrate undoped TiO 2 nanoparticles and N-doped TiO 2 nanoparticles to be the potent candidates against diabetes mellitus. Previously, Stevia rebaudiana loaded TiO 2 nanoparticles have been proved potential antidiabetic agents via in vivo studies performed in rats [40]. N-doped TiO 2 nanoparticles possess more significant α-amylase inhibition (38.2%) as compared to bare TiO 2 nanoparticles (24.8%).…”
Section: Resultsmentioning
confidence: 99%
“…After 31 days of treatment, there was a significant and permanent decrease in blood glucose, glycosylated hemoglobin, TC, and TAG, along with a higher insulin concentration (P < 0.01) in animals treated with extract-loaded nanomaterial (20 and 30 µM) compared to the diabetic group treated with TiO 2 nanomaterial alone. TiO 2 nanomaterial could provide a sustained and controlled release of the plant extract which resulted in prolonged stimulation of insulin secretion (Langle et al, 2015). The previous study has shown nanoencapsulated stevioside in pluronic-F-68-poly-lactic acid (PLA) interestingly increased intestinal absorption, bioavailability, and provided a controlled release of the active component (Barwal et al, 2013).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Titanium nanoparticles have been produced by using titanium n-butoxide (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 ), metatitanic acid (TiO(OH) 2 ), titanium dioxide powder (TiO 2 ), or titanium tetraisopropoxide (Ti[OCH(CH 3 ) 2 ] 4 ) as a source of titanium ions and mixed with plant extracts [ 275 , 276 , 297 , 301 ]. Samyuktha et al prepared them using Azadirachta indica leaf aqueous extract and titanium dioxide powder.…”
Section: Current Lipid- and Inorganic-based (Metal Or Metal Oxide) Na...mentioning
confidence: 99%
“…Their investigations on diabetic rats showed powerful and prolonged antidiabetic activity. Thus, they concluded that TiO 2 can be considered a suitable vehicle for the continuous release of active compounds in the treatment of diabetes [ 276 ].…”
Section: Current Lipid- and Inorganic-based (Metal Or Metal Oxide) Na...mentioning
confidence: 99%